(untitled) (International Journal of Engineering and Computer Science, 2014)
Cloud computing is growing rapidly, with applications in almost all the areas. SaaS (Software as a Service) is a modern approach to deliver large scalable enterprise software as a service on Internet. Cloud platform provides the scalability, availability and utility computing for services on Internet. There are many technical challenges involved in SaaS development. One of them is multi-tenancy, which allows single instance of software to serve multiple organizations by accommodating their unique requirements through configuration at the same time. SaaS architecture requires the both configuration and some level of customization to achieve higher maturity model. As every organization requires a Management Software to run their business, as they have been using traditional on-premise software which usually requires many hardware and software resources. There are many organizations that cannot afford such investments and cloud computing is the best solution. In this paper, we will explore the customization issues and challenges to SaaS vendors; we proposed an application model in which we can use xml data type in database to make customizations more flexible